UROPANC trial: Unveiling a new era in pancreatic cancer detection and treatment - Mya Briscoe (BioScientist: The Salford Biomedicine Society Magazine, 2024)
This article explores the UROPANC trial's innovative approach to early detection and treatment of Pancreatic Ductal Adenocarcinoma (PDAC), a cancer known for its late diagnosis. Led by Professor Crnogorac-Jurcevic at the Queen Mary University of London, the trial is a beacon of hope in oncology, potentially revolutionising PDAC management. At its core is the PancRISK algorithm, which utilises a urinary biomarker panel including REG1B, LYVE1, and TFF1 to detect PDAC cancer before metastasis. These biomarkers present a non-invasive, cost-effective method for early-stage PDAC detection. Involving over 3,000 symptomatic and asymptomatic participants, the trial aims to validate these biomarkers in conjunction with the traditional CA19-9 marker. This method could significantly enhance early detection, improving treatment outcomes and survival rates. This article delves into the trial's methodology and the broader implications of its findings. The UROPANC trial represents a significant leap in PDAC management, and a paradigm shift in the detection and treatmentof one of the most challenging forms of cancer.
Keywords: pancreatic oncology; pancreatic ductal adenocarcinoma; PancRISK; CA19-9; urine biomarkers; REG1B; TFF1; distal cholangiocarcinoma; UROPANC trial